Field notes contributed by Peter C. Petersen, fall 1987 - Petersen, Peter C.et al (1987)
Fall report of birds and locations contributed by Peter C. Petersen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. Epson - sheet feed/flatbed